The ethics of educational research (Blackwell, 2002)
In this volume, philosophers and social scientists shed new light on the ethical issues confronted by educational researchers. * Offers fresh insights into the conflicts and dilemmas emerging from educational research practices. * Maps out the conceptual terrain of research ethics. * Gives philosophical substance to discussions about the ethics of research.